DA'WAH BIL IHSAN; CONCEPT, METHODS, AND APPLICATION - Abdul Kadir (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2022)
Research Objectives: This study aims to reveal the bil ihsan da'wah model. A da'wah model based on knowledge, patience and love. Research Methods: Qualitative. Research Results: First: Da'wah bil ihsan prioritizes knowledge, love and gentleness. So that originally hate turned into love. The word ihsan itself is mentioned in the Qur'an in several places. Both are done by way of ihsan, in the best way. Because this is important for preachers to do. The success of preaching or appeals depends on the extent to which the preachers understand the intricacies related to their da'wah. Scholars mention that there are several main elements in carrying out da'wah, including; Da'wah interpreters, da'wah objects, da'wah materials and uslub da'wah or methods or methods of da'wah. The basic elements of da'wah mentioned are very important in supporting the success of da'wah. be delivered. Sometimes da'wah is not successful, one of the reasons is the lack of the preacher paying attention to the elements and main points of the da'wah above. Third: understand and pay attention to the four provisions of the da'wah interpreter that must be considered. Fourth: Paying attention to the object of da'wah. Or who is he dealing with, knowledgeable people or people who are not knowledgeable. Fifth: You should use the correct da'wah method. Sixth: paying attention to the five sources of da'wah. Seventh: Pay attention to the principles of da'wah. Eighth: Done gently and wisely, that is da'wah bil ihsan.